Estudio de factibilidad para la creación de una microempresa artesanal dedicada a la elaboración y comercialización de yogurt de jackfruit en la ciudad de Quevedo, a partir del año 2013” - Carrera Cedeño, Lisbeth Carolina (2013)
It has made a feasibility study for the design of a craft micro-enterprise dedicated to the making and merchandising of yogurt of the jackfruit fruit in Quevedo city, province of Los Rios. Beginning of the marker study, it design production technical study and economic analysis financial, in order to use the raw material available. This project is in to give to the yogurt the importance which has the nutritional quality, contributing so to satisfy the high demand currently exists for functional foods, this in turn will strengthen the economy of the area, to generate working place, to increase the economic level of the population and to improve the life style. With a detailed study per capita consumption of milk and its derivatives can be analyzed that these products are consumed by the vast majority of the Ecuadorian population. The investment will be directed to the acquisition of machinery, equipment and materials needed for achieving to consolidate the production and marketing operations for the company required for normal development of the activities of production and sale of the product. According to the financial analysis is expected to profit from the first year to a value of $ 8.413,20, for the second year, profit increases to $ 15.967,62, reaching for the fifth year, the sum of $ 46.546,80; which shows the great performance income produced by the company. The initial investment required for the implementation of the project is $ 40.862,33. According to market research, technical, economic and financial, the project is feasible, because it reflects the following values: an internal rate of return (IRR), attractive enough 31%, when compared to the minimum acceptable rate of return (MARR), which according to the calculations is 21,11%. A Net Present Value (NPV), indicates that the project will generate a wealth of $ 12.941,86 over the life of the project, a Cost Benefit, indicating project is profitable because it has a cost benefit ratio (RB / C) of $ 1,18, which means that for every dollar invested by the investors will get 0.18 cents long-term recovery and a recovery period of investment (RPI) 4 years, 4 months and 9 days. The results obtained in different studies and the evaluation made by economic indicators show that it is feasible to create a company dedicated to the development and marketing of yogurt.